Effect of removal of vitamin-trace mineral premix and calcium and phosphorus supplements from grower and finisher diets on broiler performance - Durand, S.I.=700 1 Gernat, A.G.; Murillo, J.G.
(Es, En)
Ilus., 16 ref.
Keywords: POLLO DE ENGORDE; NUTRICION ANIMAL; CALCIO; FOSFORO; OLIGOELEMENTOS; VITAMINAS; HONDURAS; MINERALES TRAZA